Environmental attitudes of European tourists: A multilevel analysis - Campos-Soria, Juan Antonio; García-Pozo, Alejandro; Sánchez-Ollero, José Luis (My University, 2015)
Literature shows that heterogeneity in willingness to pay for traveling is explained by regional clusters because not all the tourists are equally sensitive to income and price adjustments. This paper demonstrated that such heterogeneity in tourist behavior is also shown in environmental considerations when they are making decisions about their holiday plans. Popular support for environmental protection among tourists from EU-27 countries were investigated. The findings are congruent with the hypothesis that environment support depends not only on individual characteristics of themselves but also of certain contextual variables related to their place of residence.
Keywords: Turismo; Environment; Tourism attitudes; Multilevel analysis